A resistive-feedback LNA in 65 nm CMOS with a gate inductor for bandwidth extension. Issue 1 (January 2015) - Huang, Dong; Diao, Shengxi; Qian, Weiqiang; Lin, Fujiang
Abstract In order to get a wideband and flat gain, a resistive-feedback LNA using a gate inductor to extend bandwidth is proposed in this paper. This LNA is based on an improved resistive-feedback topology with a source follower feedback to match input. A relative small inductor is connected in series to transistor׳s gate, which boosts transistor׳s effective transconductance, compensates gain loss and then leads the proposed LNA with a flat gain and wider bandwidth. Moreover, the LNA׳s noise is partially inhibited by the gate inductor, especially at high frequency. Realized in standard 65-nm CMOS process, this LNA dissipates 12 mW from a 1.5-V supply while its core area is 0.076 mm2. Across 0.4–10.6 GHz band, the proposed LNA provides 9.5±0.9 dB power gain (S21), better than −11-dB input matching, 3.5-dB minimum noise figure, and higher than −17.2-dBm P1 dB.